Post-Conflict Reconstruction: The Changes in Relations between Government and Non-Governmental Organizations (Czech Journal of International Relations, 2008)
Non-governmental organizations participate more than two decades onpost-conflict reconstruction and peace-building. They participated onreconstruction of Bosnia and Herzegovina, Angola and Haiti. Existingexperiences with post-conflict reconstruction shows that NGOs play apositive roles in the process. On the basis of analysis of post-conflictreconstruction in various countries the author thinks that the positiverelationship between NGOs and governments by the post-conflictreconstruction and peace-building is weakening. Why after more thandecade of successful evolution of relationship between NGOs andgovernments in the process of post-conflict reconstruction the skepticismabout this relationship emerges? On the case study of post-conflictreconstruction of Afghanistan the possible answer will be offered.
Keywords: Afghanistan; government; non-governmental organizations; peace-building; postconflict reconstruction